2019
DOI: 10.1108/pr-10-2018-0408
|View full text |Cite
|
Sign up to set email alerts
|

Work–life programmes and organisational outcomes: the role of the human resource system

Abstract: Purpose Empirical findings on the link between work–life programmes and organisational performance have been inconsistent, demanding further investigation of contextual factors. The paper aims to discuss this issue. Design/methodology/approach This study uses social exchange theory, strategic human resource (HR) management theory and stakeholder theory to examine the relationship between work–life programmes and organisational outcomes, using three performance measures: perceived organisational performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 124 publications
0
14
0
1
Order By: Relevance
“…The third phase focuses on monitoring stakeholder relationships, including modifying strategies and plans. Monitoring and modifying stakeholder relationships help managers know where to focus their attention in order to align work-life programs, such as WFA, with human resource systems (Akter et al. , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The third phase focuses on monitoring stakeholder relationships, including modifying strategies and plans. Monitoring and modifying stakeholder relationships help managers know where to focus their attention in order to align work-life programs, such as WFA, with human resource systems (Akter et al. , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the literature review found that a good work-life balance and consistent working conditions improve the performance of organisations (Hyman et al , 2003; Turner et al , 2009; Murphy and Doherty, 2011). Moreover, work life programmes are positively associated with performance (Soomro et al , 2018; Akter et al , 2019). Nevertheless, we find that in UKBRs workers find it hard to balance work and family life, and have to work in unhealthy working conditions, which negatively affects their performance.…”
Section: Discussionmentioning
confidence: 99%
“…The effect size is similar when focusing on partial policies and on the use of WLB policies in general. For example, Akter et al. (2019, 2021) measured the presence of WLB policies using a 23- item questionnaire asking about a range of WL programs available in the organization.…”
Section: Methodsmentioning
confidence: 99%